Some characterisations of groups in which normality is a‎ ‎transitive relation by means of subgroup embedding properties - Ramon Esteban-Romero (International Journal of Group Theory, 2018)
‎In this survey we highlight the relations between some subgroup embedding properties that characterise groups in which normality is a transitive relation in‎ ‎certain universes of groups with some finiteness properties‎.